Competitive wetting of acetonitrile and dichloromethane in comparison to that of water on functionalized carbon nanotube surfaces - Debgupta, Joyashish; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Differential wetting of pristine and ozonized carbon nanotubes has been studied using solvents like acetonitrile and dichloromethane in comparison to the well-known wetting behavior of water. Based on their unique structural and physical properties, functionalized CNT substrates have been used due to the fact that independent variation in molecular as well as electronic properties could be controlled by understanding the wetting of these liquids on carbon nanotubes (CNTs), both pristine as well as ozone treated. The sensitivity of the wetting behavior with respect to molecular interactions has been investigated using contact angle measurements while Raman and XPS studies unravel the differential wetting behavior. Charge-transfer between adsorbed molecules and CNTs has been identified to play a crucial role in determining the interfacial energies of these two liquids, especially in the case of acetonitrile. Ozone treatment has been observed to affect the surface properties of pristine CNTs along with a concomitant change in the wetting dynamics.